Omogočanje pravilnega sedenja ob izvajanju aktivnosti za osebe z nevrološkimi okvarami - Švajger, Andreja (Rehabilitacija (Ljubljana), 2019)
In rehabilitation programs, occupational therapists focus, among other things, on enabling correct seating for persons with neurological conditions. Active seating and positioning of children can be achieved by counselling and choosing adapted seats, wheelchairs and other equipment. In adults, good posture is crucial for stable and balanced position that enables occupational performance and reduces injury risk. In home and work environment, correct seating is enabled by choosing and adapting furniture, especially seats and tables. Specific seating and positioning for computer work and reducing continuous sitting time also need to be considered. Training persons to establish, maintain and adapt seating posture independently is also important.
Keywords: assistive technology; biomechanics of seating; Biomedical Technology; biomehanika sedenja; body posture; delovna terapija; Occupational therapy; podporna tehnologija; seating; sedenje; telesna drža